Partial atomic and Ionic stopping powers of gaseous hydrogen for helium and hydrogen beams. - Cuevas, J.; Garcia Muñoz, M.; Torres, P.; Allison, S. K. (American Chemical Society, 1964)
Fil: Cuevas, J. Comisión Nacional de Energía Atómica; Argentina